2022
DOI: 10.1021/acs.jchemed.2c00328
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Laboratory Chemistry Learning and Teaching Must be Accessible

Abstract: This commentary is a call to make the future of chemistry laboratories accessible and inclusive. We draw from research and lived experience to put forward a list of recommendations for laboratory-based teaching. Our authorial team includes undergraduate and postgraduate chemistry students, graduate teaching assistants, teaching-focused and traditional research and teaching academics, and a Diversity Equality Inclusion (DEI/EDI) academic expert. We all have lived experiences of disability, chronic illness, neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The investigation of the students' answers indicated that no accessibility barrier was found in the didactic material. This result is appropriate to the recommendations ofEgambaram et al (2022).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…The investigation of the students' answers indicated that no accessibility barrier was found in the didactic material. This result is appropriate to the recommendations ofEgambaram et al (2022).…”
mentioning
confidence: 52%
“…The selection of the components applied in the video was made taking into account the specificities of inclusive education (Egambaram et al, 2022). The choice of images was made in order to add didactic value to the BVM, also aiming to arouse students' interest in the discipline of Chemistry and make the content more interactive.…”
Section: Creation and Validation Of Bilingual Educational Videos Abou...mentioning
confidence: 99%
“…11) Other clusters have been formed, including the Disability/Chronic Illness/Neurodivergence Cluster which led a funded project on lab accessibility. 12) Following the success of these clusters, further Community Clusters are planned in response to the needs of the community, including a 1 st Generation Cluster for supporting those who are the 1 st generation in their family to attend a higher education institution, and an LGBTQIA+ Cluster.…”
Section: Community Clustersmentioning
confidence: 99%
“…The chemical laboratory is an important component of any degree 2 but is typically not inclusive and accessible. 3 Physical impairments such as hearing loss 4 and visual impairment 5−8 are challenging, but solutions can be envisaged and enacted; however, more subtle challenges such as neurodiversity 9 are far more difficult to identify and resolve. It is noted that the laboratory is an environment that can overload the senses for both learner and instructor.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Defining disability, for example, is difficult, with a wide range of areas to consider, but “disability” is not the only issue to address in the Chemical Sciences. The chemical laboratory is an important component of any degree but is typically not inclusive and accessible . Physical impairments such as hearing loss and visual impairment are challenging, but solutions can be envisaged and enacted; however, more subtle challenges such as neurodiversity are far more difficult to identify and resolve.…”
Section: Introductionmentioning
confidence: 99%